Analisis Sikap Uni Eropa Menolak Deklarasi Kemerdekaan Catalonia dari Spanyol (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2023)
The European Union as a regional organization in Europe, has a major role in all policies and decisions taken. The European Union in declaring a political stance certainly has deep considerations to maintain political stability and security in the region. The European Union also expressed its position regarding Catalonia's 2017 declaration of independence from Spain. This research uses qualitative research methods and Regional Security Complex Theory as analytical tool. This research shows the factors behind the policy of the European Union to reject the declaration of independence of Catalonia, starting from the location of Catalonia which is considered strategic, Catalonia's interactions are not going well with the European Union and its members, the paradox of separatism, international political stance, and current issues such as Brexit, separatism in Europe and the refugee crisis.